The current landscape of systemic therapy for recurrent glioblastoma: A systematic review of randomized-controlled trials. (January 2022) - Fazzari, Francesco G.T.; Rose, Foster; Pauls, Mehrnoosh; Guay, Evelyne; Ibrahim, Mohammed F.K.; Basulaiman, Bassam; Tu, Megan; Hutton, Brian; Nicholas, Garth; Ng, Terry L.
Graphical abstract: Highlights: The optimal systemic therapy for recurrent glioblastoma (rGBM) is unclear. Single study linkages and population heterogeneity prevent network meta-analysis Median OS of chemo-, immuno-, antiangiogenic, and targeted therapies: 3–17.6 mo No clearly superior regimen was identified in this systematic review Abstract: Aim: Conduct a systematic review of the effectiveness of systemic therapies for adult recurrent glioblastoma (rGBM). Methods: We electronically searched for randomized controlled trials from three major databases and four conferences from 2009-Dec 2020. Two independent reviewers conducted screening, data extraction, and quality assessment. Results: 48 randomized trials were identified. Outcome reporting was inconsistent: overall survival (OS) in 46 studies, progression free survival in 37 studies, 6-month PFS in 30 studies, objective response rate in 28 studies, and 6-month OS in 7 studies. Network meta-analysis was not feasible due to heterogeneity in outcome reporting and single-study linkages. Most studies compared lomustine (8 studies), bevacizumab (18), or temozolomide (8) with other treatments. The median OS across all studies ranged from 3 to 17.6 months. Conclusions: Based on level one evidence, there is no superior systemic regimen for rGBM. rGBM is a heterogeneous population with no single regimen demonstrating OS benefit. Registration number: CRD42020148512